2019
DOI: 10.1007/s00268-019-05021-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors, and Natural Outcome of Vocal Fold Paresis in 920 Thyroid Operations with Routine Pre‐ and Postoperative Laryngoscopic Evaluation

Abstract: Background The aim of this study was to determine the incidence, risk factors, and spontaneous recovery rate of vocal fold paresis (VFP) with routine laryngoscopy before and after thyroid surgery. Methods All consecutive patients undergoing primary or redo thyroid surgery between years 2011-2016 were prospectively registered in an electronic database, and scheduled for pre-and postoperative laryngoscopic vocal fold inspection by otolaryngologists independently of the surgical team. Results A total of 920 thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Furthermore, we reviewed complications of our patients in VANS. Postoperative RLNP is the most common complication in thyroid surgery; the reported incidence ranges between 1.4% and 6.3% [ [21] , [22] , [23] , [24] ]. In our series, RLNP was noted in 4 patients (5.7%) including permanent palsy in 1 case (1.4%); the incidence ratio was considered to be no different from reports of conventional surgery, which is considered about 3% to 6% [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we reviewed complications of our patients in VANS. Postoperative RLNP is the most common complication in thyroid surgery; the reported incidence ranges between 1.4% and 6.3% [ [21] , [22] , [23] , [24] ]. In our series, RLNP was noted in 4 patients (5.7%) including permanent palsy in 1 case (1.4%); the incidence ratio was considered to be no different from reports of conventional surgery, which is considered about 3% to 6% [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 Our overall rate of paralysis was 11.1%. Many studies chose 1 year to follow the progress of vocal fold recovery, which might explain their paralysis rate since recovery is unpredictable and might take longer than 6 months to recover 5,[19][20][21][22] ; it can even take up to 2 years to recover. 21 Of note, it is worth mentioning that our definition of recovery is a bit stricter than other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a study by Caulley et al [ 23 ], thyroid cancer turned out to be the most important risk factor for phonation disorders. A study by Heikknen et al involving 920 operations showed that thyroid cancer increased the risk of complications three-fold, and that among all the factors, it was the most significant [ 24 ]. An analysis of risk factors for complications conducted by Gunn et al in 2020 based on a group of 11,000 patients showed that thyroid cancer was a statistically significant factor in vocal cord paralysis (OR = 2.1; p < 0.001) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could explain our results, which showed that age was significant for the occurrence of transient but not permanent paralysis. Permanent paralysis is most often the result of irreversible mechanical damage during thyroid surgery [ 24 ].…”
Section: Discussionmentioning
confidence: 99%